US1 Aroostook the first hundred miles of America. - Accompany (Concord, N.H. : Accompany, 2001)
"People, potatoes, paper, ployes." Documentary film about US Route 1 as it traverses Aroostook County, the most northerly portion of the highway, meeting interesting faces, stories and landmarks along the way.
VHS.
Keywords: Roads -- Maine -- Aroostook County; Roads -- United States; United States Highway 1.; Aroostook County (Me.) -- Description and travel -- 1981-